Language. Culture. Discourse - Kyrysiuk, Anastasiia (PC TECHNOLOGY CENTER, 2022)
The monograph represents a new interpretation of the relationship between the phenomenon of a Man and the triad of LANGUAGE – CULTURE – DISCOURSE.